Go0pJAKARTA SAHABAT AIR SEBAGAI KONSEP SUSTAINABLE DEVELOPMENT GUNA MENGATUR KESELARASAN ANTARA LANDUSE DAN HUMAN ACTIVITY - Lisan, Ahmad Rif’an Khoirul; Anggraini, Dhika Dwi; Rochim, Nur; Wicaksono, Ghalih Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Flooding in Jakarta has become an annual problem and also a national problem. Various factors causing flooding in Jakarta among other conditions which form the basin morphology Jakarta and many a former swamp area. The best way of dealing with flooding is the adaptation and friends with flooding. This is because in morphology, Jakarta will always inundated by floods. One form of adaptation and bersahabar with floods submerging parts of Jakarta is often flooded and make it as a city of water. City water Jakarta able to be the best solution for the future is predicted rising sea levels will be higher with the greater intensity of floods. The concept will provide other benefits such as the potential of tourism as well as other water cities in the world. This concept is based on the premise that development needs to see and recognising that the natural conditions can be done in a sustainable manner. Thought to be the concept is not done arbitrarily and written based on various studies and reports that can be proved. This concept is more realistic and better able to be implemented. The hope is that the concept of overcoming this flood to be a solution that is acceptable to the parties concerned and be that ideas from the nations children. Moreover, this concept is not only made to be a mere discourse but it is proper to be applied for the common good.Keywords: Jakarta, Flood, City Water, Morphology, Land Decline